An Analysis of the Role of Supplier Relationship Management in Enhancing Procurement Performance in the Mining Industry: A Case Study of FQM Trident Zambia (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study analyses the role of Supplier Relationship Management (SRM) in enhancing procurement performance at FQM Trident Zambia, a major mining company. Drawing on survey data from 96 procurement professionals, the research identifies the most prevalent SRM practices, assesses their impact on core procurement performance indicators, and explores implementation challenges. The findings show that long-term contracts (100%), strategic partnerships (87.5%), and regular feedback and communication (81.3%) are the most widely adopted SRM practices. Statistical analysis using chi-square tests revealed a significant positive association between SRM integration and cost efficiency (χ² = 13.12, p = 0.041), as well as delivery timeliness (χ² = 17.09, p = 0.009). Specifically, 62.5% of respondents rated procurement cost efficiency as "Good," and 56.2% rated delivery timeliness as "Good." Product quality was rated "Good" by 56.2% of respondents, though the association with SRM integration was not statistically significant. The majority (62.5%) believed SRM had "significantly improved" overall procurement performance. Key challenges cited were limited supplier cooperation (37.5%), lack of internal capacity or training (25%), and resistance to change (25%). The study concludes that while SRM has delivered measurable benefits in cost and delivery, further advances in quality and reliability will require greater investment in training, process standardization, and supplier engagement. These findings offer data-driven guidance for mining organizations aiming to achieve procurement excellence through SRM.